ANOTHER RETURN NUT, FOR THE PURPOSE OF THE "TERROR"STALINIST (1936-1938) - Saborido, Mercedes; Saborido, Jorge (Revista de Historia Social y de las Mentalidades, 2019)
The paper proposes an approach to some of the recent interpretations of the massive repression that was carried out in the Soviet Union in the middle of the decade of 1930. With this idea, aims to highlight the persistence and deepening of the academic debate after the opening of the archives that accompanied the crisis process and collapse of the soviet experience.
Keywords: Stalinism; Dictatorship; Ression; Revisionism; Post-revisionism